1971
DOI: 10.1021/jo00823a010
|View full text |Cite
|
Sign up to set email alerts
|

Gibbane synthons via hexahydrofluorenones. Intramolecular Reformatsky reaction

Abstract: An efficient synthesis of hexahydrofluorene-2,9-dione and 7-methoxyhexahydrofluorene-2,9-dione from the appropriate phenylpyruvic acids is described. Their conversion to -bromo esters and amides as well as the intramolecular Reformatsky reaction of these substances to provide gibbane synthons is detailed.Synthetic efforts directed toward the gibberellins [gibberellic acid (1)] have led to known gibberellins,3 degradation products thereof,4 and gibbane synthons.5 Our interest in this problem lay in devising an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

1972
1972
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…A related strategy based on the cyclization of vinyl halides to a carbonyl function was reported shortly after. While the Grignard reagent derived from 128 75 failed to give any bridged compound, the corresponding cuprate gave the tricyclic methylene ketone 129 in 60% yield. 76 This methodology was also employed for a more direct access to ketone 127 77 and used in a total synthesis of gibberellic acid.…”
Section: Reductive Cyclizationsmentioning
confidence: 99%
“…A related strategy based on the cyclization of vinyl halides to a carbonyl function was reported shortly after. While the Grignard reagent derived from 128 75 failed to give any bridged compound, the corresponding cuprate gave the tricyclic methylene ketone 129 in 60% yield. 76 This methodology was also employed for a more direct access to ketone 127 77 and used in a total synthesis of gibberellic acid.…”
Section: Reductive Cyclizationsmentioning
confidence: 99%
“…Cheng postulated that the abeo-abietanes found in T. cryptomerioides arise from a pinacol-type rearrangement of 6,7-dihydroxyferruginol (19), possibly derived from 6,7-dehydroferruginol (20), which is also found in the leaves of T. cryptomerioides (Scheme 1). 2a This kind of rearrangement gives rise to the 5(6f7)abeo- † Taken in part from the Ph.D. dissertation of Joel M. Shimkus, University of Georgia, Athens, GA (2009).…”
Section: Biosynthesis and Classificationmentioning
confidence: 99%
“…18 Ziegler and Condon used the PPA cyclization of phenylcyclohexanecarboxylic acid derivatives to construct their gibbane synthons (35 f 36, eq 4). 19 Ramana extended the methodology of Dev, Rand, and Conia by reacting ethyl cyclohexene-1-carboxylate (37) with variously substituted methoxylated arenes under acidic conditions (eq 5). 20 Interestingly, Ramana found that the use of H 2 SO 4 caused Michael addition to occur first, followed by intramolecular Friedel-Crafts acylation, whereas the use of PPA caused 1,2addition to the ester to take place, followed by a Nazorov cyclization.…”
Section: Synthetic Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…55%) erhalten werden. [97] Die Kupplung des lithiierten Esters Es sind zwei Methoden zur Darstellung in der Literatur beschrieben. Bei der ersteren handelt es sich um eine oxidative Diolspaltung des Weinsäuremethylesters (134), der mit Periodsäure zum Glyoxylester 135 reagiert.…”
Section: Synthese Des Substrats Für Die Domino-reaktion Unter Verwend...unclassified